THE EFFECTIVENESS OF ADMINISTRATION OF GREEN BEAN JUICE ON THE EFFECTIVENESS OF BREAST MILK IN PUBLIC MOTHERS IN WORKING AREA UPT PUSKESMAS SIMPANG TIGA PEKANBARU CITY (Proceedings OPTIMAL, 2024)
Breast milk (ASI) is the single most perfect food for babies in the first 6 months of growth, without any additional drinks or food. Green bean juice is a type of drink that contains lactagogum, a nutrient that can increase and facilitate breast milk production. The aim of this research is to determine effectivenessProviding Green Bean Juice to the Smoothness of Breastfeeding for Postpartum Mothers in the UPT Working Area of Simpang Tiga Health Center, Pekanbaru City, Riau Province. Which will be carried out in September-December 2023. This type of research is Quasy Experimental with a One Group Pretest Posttest design. The total population is 16 respondents and the samples taken are the entire population, namely 16 respondents using the Total Sampling sampling technique. The research instrument uses an observation sheet. The statistical test uses a paired sample test with a p value